INFECTIONS ON DIFFERENT CHEMOTHERAPY CYCLES IN ADULT PATIENTS WITH ACUTE LYMPHOBLASTIC LEUKEMIA TREATED WITH ALL-2009 PROTOCOL - V. A. Okhmat; G. A. Klyasova; E. N. Parovichnikova; V. V. Troitskaya; E. O. Gribanova; A. O. Malchikova; A. G. Korobova; I. N. Frolova; V. G. Savchenko (Онкогематология)
The aim of this study was to evaluate incidence and type of infections in patients with acute lymphoblastic leukemia (ALL) treated with ALL-2009 protocol during different chemotherapy cycles.Materials and methods. Prospective study (2013–2015) included patients with de novo ALL, receiving chemotherapy with ALL-2009 protocol. Patients were followed for 6 month. Total of 44 patients with ALL aged 17–61 years (median age 26 years) were enrolled in the study. These patients received 272 chemotherapy cycles (51 – induction, 221 – consolidation). On admission to  National Research Center for Hematology hyperleukocytosis was in 25 % of patients, ECOG score ≥ 3 – in 61 %, severe infections – in 22 %, hospitalization to intensive care unit (ICU) – in 9 %.Results. Neutropenia was in 91 (38 %) of 272 chemotherapy cycles, predominantly in induction (71 %) compared to consolidation (25 %), odds ratio (OR) 7.2; p <0.0001. Median duration of neutropenia was more prolonged in induction compared to consolidation (24 vs 7 days; p <0.0001). Patients were transferred to ICU in 4 % of chemotherapy cycles, predominantly in induction (18 %) then in consolidation (0.5 %; OR 47.1; p <0.0001).Mean number of infections was 1.1 (0–3) per patient and 14 (32 %) of 44 patients did not receive any antibiotics throughout all study period (6 month). Febrile neutropenia occurred in 18 % of chemotherapy cycles, and more frequently in induction compared to consolidation (55 % vs 10 %, OR 5.9, p <0.0001). The majority of febrile events were attributable to clinically documented infections (47 %), followed by fever of unknown origin (29 %) and bloodstream infection (BSI) (24 %). Clinically documented infections were represented by pneumonia (35 %) and cellulitis (12 %). Gram-negative and Gram-positive bacteria accounted for 67 % and 33 % of BSI pathogens (n = 15), consequently. Invasive mycoses (IM) were in 14 % of patients. The main IM was invasive aspergillosis (9 %). All cases of invasive aspergillosis occurred in induction. None cases of IM caused by molds were observed in consolidation.Conclusions. Our study demonstrates relatively low incidence of infections on different chemotherapy cycles in ALL patients treated with ALL-2009 chemotherapy protocol and 32 % of patients did not receive any antibiotics throughout all study period (6 month). Bacterial and fungal infections prevailed in induction compared to consolidation. The predominant IM was invasive aspergillosis. All cases of IM caused by molds occurred in induction.